CATALYTIC PERFORMANCE FOR OXIDATIVE COUPLING OF METHANE OVER EU2O3 CATALYSTS PROMOTED BY ALKALINE EARTH FLOURIDES - Ruiqiang L.; Huilin W. (My University, 1997)
The catalytic performance of oxidative coupling of methane(OCM) over Eu2O3 catalysts promoted by alkaline earth fluorides was studied. The results showed that C2 hydrocarbon selectivity and yield over the fluoride-promoted Eu2O3 catalysts were apparently higher than those over pure Eu2O3; the OCM performance increased according to the sequence of CaF2-Eu2O3 ≈ BaF2-Eu2O3 < SrF2-Eu2O3 under the same conditions. XRD experiment indicated that rhombohedral EuOF phase formed in the fresh BaF2-Eu2O3 catalyst, while the exchange of F- and O2- did not apparently happen in the fresh GaF2-Eu2O3 and SrF2-Eu2O3 catalysts. Pyridine-TPD and CO2-TPD measurements found that, after adding SrF2 to Eu2O3, the catalyst surface acidity decreased, whereas the surface basic strength increased slightly, resulting in an improvement in C2 selectivity and yield.